My story: Pompeii - Reid, Sue (London, England : c)
A fascinating fictional diary from a best-loved series- Describes the eruption of Vesuvius in a vivid account- Captures how it felt to live through this key moment- Inspiring historical reading that supports the curriculum- Hugely popular series with over a million copies sold
Say hello to yesterday without a Tardis. Discover My Story: the series where history gets real. August, AD78. Claudia is at the Forum in the great Roman city of Pompeii. It$1 (Bs a day of strange encounters and odd portents. When the ground suddenly shakes, Claudia senses that it$1 (Bs a bad omen. Why does she feel so disturbed by Vesuvius, the great volcano that looms over the city? Go back in time to a great city of the Roman Empire as it is struck by the terror of an epic disaster$1! =s